2024
DOI: 10.4317/medoral.26047
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, clinical, and prognostic analysis of oral squamous cell carcinoma diagnosed and treated in a single hospital in Galicia (Spain): a retrospective study with 5-year follow-up

I. Amezaga-Fernandez,
JM. Aguirre-Urizar,
JM. Suárez-Peñaranda
et al.

Abstract: Background Oral cancer is a common neoplasm worldwide, mostly corresponding to squamous cell carcinoma (OSCC). Unfortunately, its overall prognosis remains poor, with no improvement in recent decades. In this study, we have analysed the epidemiological, clinical, and prognostic characteristics of OSCC on patients of a specific Spanish region (Galicia), in order to improve its prognosis and apply effective preventive and early diagnosis measures. Material and Methods We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…For example, studies from the UK found that only 4.6% [25] and 6% [26] of oral cancers had arisen from previously recognized, site-specific precursor lesions that had been biopsied over a 12-and 20-year period, respectively. A higher prevalence of over 20% was recently found in European countries, such as Sweden [27] and Spain [28], although it is uncertain whether these OPMDs were biopsied and histopathologically proven. The figures derived from real-world evidence in Taiwan-a territory with one of the highest rates of OSCCs globally-are similar, with the prevalence of OSCCs preceded by OPMDs ranging between 9.9% and 15.7% (depending on how the data are interpreted) [29].…”
Section: How Many Oral Cancers Are Preceded By An Opmd?mentioning
confidence: 99%
“…For example, studies from the UK found that only 4.6% [25] and 6% [26] of oral cancers had arisen from previously recognized, site-specific precursor lesions that had been biopsied over a 12-and 20-year period, respectively. A higher prevalence of over 20% was recently found in European countries, such as Sweden [27] and Spain [28], although it is uncertain whether these OPMDs were biopsied and histopathologically proven. The figures derived from real-world evidence in Taiwan-a territory with one of the highest rates of OSCCs globally-are similar, with the prevalence of OSCCs preceded by OPMDs ranging between 9.9% and 15.7% (depending on how the data are interpreted) [29].…”
Section: How Many Oral Cancers Are Preceded By An Opmd?mentioning
confidence: 99%